Perspective as an Image Technique Appeared in the Renaissance - Mamurova, Feruza Islomovna; Saydaliyev, Sayidkarim Saydinabiyevich (European Journal of Life Safety and Stability (2660-9630), 2022)
Great visual clarity of the image. The perspective of the subject creates an impression very close to that obtained by directly viewing the subject. This is explained by the fact that in perspective parallel lines are depicted converging, and in nature we also see them converging; the same segments are depicted both in perspective and in nature the less the further they are removed from the viewer.